Interference Mitigation Techniques Using UWB Pulse Shaping. (2016) - Rinija, G.N.; Menon, Meenu B.; Iqbal, Nisheena V.; Gopakumar, A.
Abstract: Wireless Body Area Network (WBAN) is an evolving area in the field of wireless communication, remote health monitoring and telemedicine. Ultra wideband (UWB) is a preferred candidate for WBAN as it provides very high data rate at minimal power consumption. Since UWB-BAN is affected by interference from existing wireless personal and local area networks, interference mitigation has become an important research issue in WBANs. This paper investigates the impact of UWB pulse shaping techniques on interference mitigation in WBAN. Through simulations, performance of different UWB pulse shaping techniques is compared in terms of their interference mitigation capability.